Pengendalian Persediaan Bahan Baku Plat Baja Menggunakan Metode Fuzzy Logic Mamdani pada Perusahaan Diffusers - Indra Lesmana; Tedjo Sukmono (Indonesian Journal Publisher, 2026)
In a production requires the right raw material inventory, in order to minimize the occurrence of overstock or outstock, an approach is needed, namely inventory control. In the diffuser company there is an overstock problem and results in high storage costs. The purpose of this study is to optimize the amount of raw material inventory in diffuser companies against uncertain demand, so as to minimize losses for companies to support economic growth and make a major contribution to the company. Fuzzy logic mamdani is used to process uncertain or vague data and decision making related to the accuracy of the amount of raw material inventory. Identifying data by determining the variables needed there are several stages, namely fuzzyfication, implication, and defuzzyfication. The results project that with a production target of 353 diffusers and facing a demand of 198 diffusers, the inventory, which was originally 419 steel plates, can be optimized with the Mamdani fuzzy logic method around 343.61 plates, rounded up to 344 steel plates. The MAPE calculation has an error value of 26,4971% and is included in the sufficient category.